The pelota locus encodes a protein required for meiotic cell division: An analysis of G2/M arrest in Drosophila spermatogenesis. - Eberhart, C.G.; Wasserman, S.A. (Development, 1995)
During Drosophila spermatogenesis, germ cells undergo four rounds of mitosis, an extended premeiotic G2 phase and two meiotic divisions. In males homozygous for mutations in pelota, the germline mitotic divisions are normal, but the cell cycle arrests prior to the first meiotic division; pelota males are therefore sterile. Chromosomes begin to condense in these mutants, but other meiotic processes, including nuclear envelope breakdown and spindle formation, do not occur. The arrest phenotype closely resembles that of mutations in the Drosophila cdc25 homolog twine. Although meiosis is blocked in pelota and twine homozygotes, spermatid differentiation continues. pelota is also required for patterning in the eye and mitotic divisions in the ovary. We have cloned the pelota locus and show it encodes a 44 x 10(3) M(r) protein with yeast, plant, worm and human homologs.